2019
DOI: 10.1002/celc.201900566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Support on the Electrocatalytic Properties of Pt−Ru Catalysts

Abstract: What prompted you to investigate this topic/problem?Pt-based electrocatalysts supportedo nc arbon substrates are widely used as anodic and/orc athodic electrodes in proton exchange membrane fuel cells (PEMFCs). Among all available carbon supports, Vulcan XC-72 is the mostused in PEMFCelectrodes. However,P EMFCs still suffer from the insufficient durability of their electrodes, owing to several degradation mechanisms for the Pt-based nanocrystallites such as metal particles detachment andd issolution, and carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…was much sought, and a few literature reports demonstrate such nanostructure-conductive support hybrids as an effective measure to enhance the overall water splitting efficiency of the electrocatalyst. 35,36 Furthermore, in situ growth of nanohybrids supported on conductive substrates can considerably minimize the particle aggregation, and eventually expose more catalytically active sites. Recently, Lin et al reported defect rich MoS 2 /NiS 2 nanohybrids supported on carbon cloth under a hydrothermal process followed by sulfudization for efficient overall water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…was much sought, and a few literature reports demonstrate such nanostructure-conductive support hybrids as an effective measure to enhance the overall water splitting efficiency of the electrocatalyst. 35,36 Furthermore, in situ growth of nanohybrids supported on conductive substrates can considerably minimize the particle aggregation, and eventually expose more catalytically active sites. Recently, Lin et al reported defect rich MoS 2 /NiS 2 nanohybrids supported on carbon cloth under a hydrothermal process followed by sulfudization for efficient overall water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, support materials can also influence both the electron and proton transfer processes; therefore, they will appreciably correlate with the catalyst performance [15]. Suitable support is beneficial for dispersing and anchoring catalyst nanoparticles, increasing the effective active area, improving the catalyst activity and stability, constructing an efficient electrocatalytic reaction interface, and reducing the cost of PEMFCs [16][17][18][19]]. An ideal catalyst support needs to possess the following properties, namely, (1) suitable pore structure, (2) high active specific surface area, (3) high conductivity, and (4) good thermal and electrochemical stability [15,16,20].…”
Section: Introductionmentioning
confidence: 99%
“…Suitable support is beneficial for dispersing and anchoring catalyst nanoparticles, increasing the effective active area, improving the catalyst activity and stability, constructing an efficient electrocatalytic reaction interface, and reducing the cost of PEMFCs [16][17][18][19]]. An ideal catalyst support needs to possess the following properties, namely, (1) suitable pore structure, (2) high active specific surface area, (3) high conductivity, and (4) good thermal and electrochemical stability [15,16,20]. Among all the promising supporting materials, carbon is the most desirable and widely adopted one because of its distinguishing features, namely, (1) high stability (in both acidic and basic media, even at high temperature), (2) controllable pore structure, (3) tractable physical form, (4) modifiable surface chemistry, and (5) low cost [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Although the carbon support plays an important role in the electrocatalysts employed in fuel cell devices, limited comparisons have been conducted to evaluate and compare fuel cell performance using different carbon supports in electrocatalysts. For example, Bjorn et al [13] experimentally investigated the influence of carbon supports such as biochar (BC), CB, GR, and CNTs on the electrocatalytic properties of Pt-Ru catalysts toward hydrogen oxidation reaction used for PEMFCs. Their results showed that the electrocatalytic activity is affected by the crystalline phase, as well as the point of zero charge.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, following our previous work [23], we employed Ag as the metal catalyst to develop non-Pt catalysts supported on carbon for the ORR in AEMFCs. In addition, different carbon supports and metals have different interactions that significantly influence the electrochemical behavior of catalysts [13]. From our point of view, more studies on the development of non-noble metal catalysts are needed to bring AEMFC technology to the market.…”
Section: Introductionmentioning
confidence: 99%